2015
DOI: 10.24042/ajpm.v6i1.51
|View full text |Cite
|
Sign up to set email alerts
|

Mengembangkan Kemampuan Koneksi Matematis Melalui Buku Ajar Elektronik Interaktif (Baei) Yang Terintegrasi Nilai-Nilai Keislaman

Abstract: Learning by using electronic textbooks should have more value than regular print books that are widely circulated. More value is there because the use of BAE must use a tool in the form of a computer (PC), e-book reader, tablet, or smartphone to open it. With the tools used, it is fitting that BAE is capable of displaying interactive simulations with added features in the form of video, animation, sound or image. This textbook is known as Interactive Electronic Textbook (BAEI). Islamic madrasahs and universiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
17

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 1 publication
0
7
0
17
Order By: Relevance
“…Then, in order to overcome the problems that have been found, interesting learning materials should be developed in the form of electronic-based learning module. The learning process by using the electronic-based learning module certainly displays the higher value in comparison to the ordinary textbooks (Supriadi, 2015).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Then, in order to overcome the problems that have been found, interesting learning materials should be developed in the form of electronic-based learning module. The learning process by using the electronic-based learning module certainly displays the higher value in comparison to the ordinary textbooks (Supriadi, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…The situation becomes worse because the language and the illustration that have been used are not communicative and interactive and, consequently, the message of the learning materials are less grasped by the students. Under such conditions of learning materials, the use of these textbooks demand supplementary teaching materials in order to achieve the student competencies (Supriadi, 2015). On the contrary, the results of the field study also show that the students from the Third Grade have been supplied with the LCD and the sound system as part of their learning materials.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, grade VII MTs Hidayatullah Batakte stated that there was a category of having completed learning, this was seen from the percentage of classical completeness which showed that there were 85.7% of students who had completed learning. One way to form noble character in learning mathematics is to design learning that is integrated with Islamic values [10], [11]. Coupled with hots-based questions can help students towards higher-order thinking skills and try to find solutions creatively so that new things are better and useful for their lives [12].…”
Section: Description Of the Assessment Phasementioning
confidence: 99%
“…Wulandari et al, 2019). Hal itu dijadikan pembeda antara pendidikan di madrasah dan Perguruan Tinggi Islam yang memiliki penerapan nilai-nilai keislaman dengan sekolah dan Perguruan Tinggi Umum (Supriadi, 2015). Pengintegrasian nilai-nilai keislaman dalam pembelajaran matematika akan dapat membentuk pribadi bangsa yang tangguh, menjiwai iman dan takwa kepada Allah SWT dengan berorientasi pada IPTEK (Sari, 2018).…”
Section: Pendahuluanunclassified
“…Selain penerapan nilai-nilai keislaman untuk pembelajaran Matematika, di Madrasah Tsanawiyah juga diperlukan penggunaan teknologi dalam proses pembelajaran atau pun di lingkungan sekolah. Penggunaan teknologi informasi dalam proses pembelajaran dapat membantu siswa dalam bereksplorasi pada materi yang dipelajari, melatih untuk berpikir sistematis, logis analisis, kritis dan kreatif, berkolaborasi dalam pemecahan masalah, serta melatih siswa untuk memanfaatkan informasi yang diterimanya (Supriadi, 2015).…”
unclassified